Green and Sustainable Approaches to the Synthesis of Pyrazole-Thiazole Hybrids Biological Activity-Focused - Niral H kalariya; Dr. Kalpesh Ganatra (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The synthesis of key intermediates and a general procedure for the synthesis of Schiff bases of pyrazoloaldehyde with 5-nitrothiazol-2-amine are described. 5-nitrothiazol-2-amine was synthesized from N, N-dimethyl-2-nitroethenamine through a series of reactions involving the use of N-bromosuccinimide and thiourea, yielding 75% of the desired product. N-Phenylamino-α-methyl-phenyl azomethine was synthesized by refluxing a mixture of phenylhydrazine and acetophenone in absolute ethanol with glacial acetic acid, resulting in a 90% yield 2 . 1-N,3-Diphenyl-4-formyl pyrazole was obtained by adding N-Phenylamino-α-methyl-phenyl azomethine to a Vilsmeier-Haack reagent, followed by refluxing and purification, with a yield of 87%. Finally, Schiff bases were synthesized by combining pyarzoloaldehyde with 5-nitrothiazol-2-amine in methanol with glacial acetic acid catalyst, yielding the title compounds with 60% yield.